Caracterização da aptidão climática da região da Campanha do Rio Grande do Sul para a viticultura - Brixner, Gabriel Franke (2013)
The climatic characterization of the producing regions with potential for vitiviniculture becomes a demand of modern viticulture. Among the new frontiers of modern viticulture it is highlighted the Campanha region located in Rio Grande do Sul, being driven for presenting soil and climatic conditions favorable for growing grapes vines. This new culture lacks studies of interference of climatic conditions in the development of the plants in the region. The dissertation aims to characterize the suitability of the climate of the region Campaign of Rio Grande do Sul for viticulture. The work was divided into three chapters, the first being a study on the estimation of the evapotranspiration by different methods and its application in the Dryness Index (DI) for the municipalities of Campanha, aiming to identify alternatives methods to the standard one (Penman-Monteith) used in the DI. In the second chapter, it was performed the climatic characterization of the region through the Geoviticulture Multicriteria Climatic Classification System, aiming to identify the thermal and hydric availability of the municipalities of the region under study. In the third chapter, it was held a study of the risk of frost and the duration of phenological subperiods of Cabernet Sauvignon in the Campanha region. In these chapters, we used daily meteorological data, the period from 1961 to 2010, for Alegrete, Bagé, Quaraí, São Gabriel, Santana do Livramento and Uruguaiana as availability of municipalities. It was found that the Thornthwaite, Camargo, Makkink and Blaney-Criddle methods present optimal performance in estimation of the evapotranspiration compared to standard when the using it with DI. It was used the Thornthwaite method for the estimation of the evapotranspiration throughout the Campanha, allowing to analyze a longer period of DI in the region, being this class of the wet type, having hydric availability for cultivation. The index of night cold is of the class of temperate nights in Campanha, however there are variations among municipalities, months and years analyzed. Regarding the heliothermal index, Uruguaiana is of the very hot kind and the other municipalities are of the hot kind, having high thermal availability, combined with climatic conditions that favor the ripening of the grapes with satisfactory condition for winemaking. Regarding the risk of frost, Uruguaiana and São Gabriel in early September have low risk of frost formation at 5% level, while in the other municipalities the last date occurs in early October, characterized as spring frosts. It is also possible to see that Cabernet Sauvignon showed variations in the total number of days in relation to sprouting periods, as well as between municipalities Campaign.